Clinical experience of the neonatal surgical unit at a highly specialized pediatric institute in Peru, 2018-2022 - Samanez-Obeso, Angel Francisco (2023)
Objective: To describe the therapeutic results of patients treated at the Neonatology Unit of the Instituto Nacional de Salud del Niño San Borja, Lima, Peru. Methods: A descriptive study was carried out where the information of the patients who attended between the years 2018 and 2022 was used, by reviewing their medical records. Results: During the evaluation period, a total of 1,134 patients were attended, with a median age of 6 days, and the majority were born outside of Lima. 92.2% received a surgical diagnosis, with structural heart defects, anorectal malformations, and small bowel atresia among the most prominent. In general, survival to discharge from our intensive and intermediate care neonatology unit was 93.7%, with an unequal distribution of deaths in patients who required transfer from cities in Peru other than Lima. Conclusion: In our experience of treating critically ill neonatal patients, we have maintained a survival like that described in high-income countries. However, it could be further improved through the application of strategies for the decentralization of specialized neonatal care and the improvement of transport systems for critically ill neonatal patients in Peru.